2003
DOI: 10.1017/s0021859603002934
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of inorganic fertilizers by organic manures and the effect on soil fertility in a rice–wheat rotation on reclaimed sodic soil in India

Abstract: involving use of NPK fertilizers alone and in combination with green manure (Sesbania bispinosa) or farmyard manure (FYM) in a rice-wheat cropping sequence. An attempt was made to evaluate the effect of the substitution of inorganic fertilizers with organic manures on yields of grain and nutrients, economy and soil fertility during 1997-98 and 1998-99. Application of NPK and its combination with green manuring and FYM increased the rice yield significantly. Applying inorganic fertilizers resulted in similar ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 7 publications
10
37
0
1
Order By: Relevance
“…Further, these results are also in concurrence with Negassa et al (2001) who found that corn yield was increased by 35% when combined (inorganic and organic) nutrients were applied. reported by Yaduvanshi (2003) that a reduction of soil pH occurs when green manure or farmyard manure was used in alkaline soils. Low pH value for FYM is very valuable for calcareous soils (Karami et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Further, these results are also in concurrence with Negassa et al (2001) who found that corn yield was increased by 35% when combined (inorganic and organic) nutrients were applied. reported by Yaduvanshi (2003) that a reduction of soil pH occurs when green manure or farmyard manure was used in alkaline soils. Low pH value for FYM is very valuable for calcareous soils (Karami et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…S. aculeate belongs to the Fabaceae, is native to Pakistan and India and is commonly grown for the reclamation of salt-affected soils. It can be used as a green manure (Yaduvanshi 2003;Kurdali 2004), to improve soil characteristics (Mandal et al 2003). Although a lot of information is available about the nutritive value of Sesbania sesban (Hossain et al 2001;Goel et al 2008) and its effect on the reproductive performance of farm animals (Mekoya 2008), little is know about S. aculeate grown on salty soil and irrigated by saline water, thus making it difficult to assess its potential contribution to sustain animal production.…”
Section: Introductionmentioning
confidence: 99%
“…cropping system (Yaduwanshi, 2003). However, the combined application of organic manure and chemical fertilizers has been shown to improve SOC in comparison to addition of inorganic fertilizer alone (Mandal et al, 2003).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 390-397mentioning
confidence: 99%